2020
DOI: 10.3892/ijmm.2020.4642
|View full text |Cite
|
Sign up to set email alerts
|

miR‑187‑3p inhibitor attenuates cerebral ischemia/reperfusion injury by regulating Seipin‑mediated autophagic flux

Abstract: MicroRNAs (miRNAs/miRs) have been reported to affect ischemia/reperfusion (I/R)-induced cerebral damage. miRNAs cause post-transcriptional gene silencing by binding to the protein-coding sequence (CDS) of mRNAs. Seipin has a potential role in regulating autophagic flux. The present study investigated the involvement of miR-187-3p in Seipin expression, autophagic flux and apoptosis in vitro , as well as the underlying mechanism, using PC12 cells exposed to oxygen-glucose deprivation/reoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Hence, we selected miR-187-3p for subsequent validation, and found that CTS-mediated phenotypic alterations in HASMCs at least in part through regulating miR-187-3p expression. The function of miR-187-3p in cancer, reperfusion injury and sepsis has now been identified [ 53–56 ]. For example, overexpression of miR-187-3p attenuates ischemia-reperfusion-induced pain sensitivity by inhibiting the release of P2X7R and subsequently mature IL-1β in the mouse spinal cord [ 55 ] miR-187-3p inhibits metastasis and epithelial-mesenchymal transition in hepatocellular carcinoma by targeting S100A4 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we selected miR-187-3p for subsequent validation, and found that CTS-mediated phenotypic alterations in HASMCs at least in part through regulating miR-187-3p expression. The function of miR-187-3p in cancer, reperfusion injury and sepsis has now been identified [ 53–56 ]. For example, overexpression of miR-187-3p attenuates ischemia-reperfusion-induced pain sensitivity by inhibiting the release of P2X7R and subsequently mature IL-1β in the mouse spinal cord [ 55 ] miR-187-3p inhibits metastasis and epithelial-mesenchymal transition in hepatocellular carcinoma by targeting S100A4 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of seipin in diseases not caused by BSCL2 mutations has attracted more and more attention in recent years. At present, the relationships between seipin and metabolic [ 16 ], neurodegenerative [ 10 , 17 , 18 , 19 , 20 , 166 ], and other diseases [ 21 , 167 , 168 ] have been reported.…”
Section: Research Advances Acquired From Diseases Associated With Abn...mentioning
confidence: 99%
“…In glioblastoma patients and glioblastoma cell lines, the expression of BSCL2 is increased [ 167 ]. In ischaemia/reperfusion-induced cerebral damage, the expression of seipin is inhibited by elevated miR-187-3p (a microRNA which can bind to the protein-coding sequence of seipin), and suppression of seipin expression increases neuronal apoptosis via deficient autophagic flux and ER stress [ 18 , 19 ]. Furthermore, SKO mice have exacerbated neurological disorder and enlarged infarct size that may be caused by increased blood–brain barrier permeability, amplified ER stress, and elevated glucose levels, as well as decreased leptin and adiponectin levels [ 170 ].…”
Section: Research Advances Acquired From Diseases Associated With Abn...mentioning
confidence: 99%
See 1 more Smart Citation
“… 9 MiR-187-3p inhibitor attenuates cerebral I/R injury through modulating Seipin-mediated autophagic flux. 10 MiR-211 protects brain against I/R injury by suppressing cell apoptosis. 11 MiR-124-5p reduces ROS production and improves the inflammatory microenvironment to protect against cerebral I/R injury by targeting NOX2.…”
Section: Introductionmentioning
confidence: 99%